Facebook's role in online reputation management - Tasențe, Tănase (Technium Social Sciences Journal, 2020)
Controlling online content with a brand, which performs well in search and social results, is considered a major force when it comes to image analysis in the online environment. Positive reviews, press coverage and other beneficial materials are also considered useful for a brand. In addition, a strong search profile, including links from authoritative sites to positive online content, is a form of advantage. In order to investigate the interaction of Facebook users, a questionnaire was prepared which was distributed and completed by online users. The role of the questionnaire is to capture users' perception of the importance they attach to their image from the perspective of their personal Facebook profile. The objectives of the study were to identify the main reasons why Internet users use the Facebook site, the frequency with which they access the social network, the most used device for logging in and the evaluation of affirmations that confirm or disprove the use of Facebook to promote the personal image. The questionnaire was distributed on the Internet and on several Facebook groups with over 50,000 members, between June 10 and 25, 2019.